Isolation of goat milk small extracellular vesicles by novel combined bio-physical methodology - González, María Isabel; Gallardo, Begoña; Cerón, Carlos; Aguilera-Jiménez, Elena; Cortes-Canteli, Marta; Peinado, Héctor; Desco, Manuel; Salinas, Beatriz (Frontiers in Bioengineering and Biotechnology, 2023)
Goat milk is notable as a cost-effective source of exosomes, also known as small extracellular vesicles (sEVs). These nanoparticle-like structures are naturally secreted by cells and have emerged as potential diagnostic agents and drug delivery systems, also supported by their proven therapeutic effects. However, the complexity of goat milk and the lack of standardized protocols make it difficult to isolate pure sEVs. This work presents an optimized approach that combines well-established physical isolation methods with the biological treatment of milk with rennet. sEVs derived from goat milk were purified using a methodology that combines differential ultracentrifugation, rennet, and size-exclusion chromatography. This novel strategy was compared with two of the main methodologies developed for isolating extracellular vesicles from bovine and human milk by means of physico-chemical characterization of collected vesicles using Transmission Electron Microscopy, Western Blot, Bradford Coomassie assay, Dynamic Light Scattering, Nanoparticle Tracking Analysis and Zeta Potential. Vesicles isolated with the optimized protocol had sEV-like characteristics and high homogeneity, while samples obtained with the previous methods were highly aggregated, with significant residual protein content. This work provides a novel biophysical methodology for isolating highly enriched goat milk sEVs samples with high stability and homogeneity, for their further evaluation in biomedical applications as diagnostic tools or drug delivery systems.